Microneedle-mediated transdermal and intradermal drug delivery - Donnelly, Ryan F. (Chichester, West Sussex : Wiley-Blackwell, 2012)
One of the latest techniques in drug delivery, microneedles are used for administering a wide range of drug substances used to treat various medical conditions. Thorough background information is included providing a history of the field. Various methods used to produce micorneedles are described as well as a snapshot of the future directions within the industry. Written by highly qualified authors, this new text is the only title providing a comprehensive review of microneedle research in the fields of transdermal and intradermal drug delivery.
Transdermal drug delivery -- Microneedles : design, microfabrication and optimization -- Microneedle applicator designs for transdermal drug delivery applications -- Transdermal delivery applications -- Microneedle-mediated intradermal delivery -- Clinical application and safety studies of microneedles -- Microneedles : current status and future perspectives.
Includes bibliographical references and index.
Print version record.
Keywords: Microinjections; Transdermal medication; Drug delivery systems; Microinjections -- methods; Administration, Cutaneous; Drug Delivery Systems; Injections, Intradermal; MEDICAL -- Drug Guides; MEDICAL -- Nursing -- Pharmacology; MEDICAL -- Pharmacology; MEDICAL -- Pharmacy; Drug delivery systems; Microinjections; Transdermal medication; Electronic books